2020
DOI: 10.1002/jmv.26300
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of blood urea nitrogen/creatinine ratio and other routine blood parameters on disease severity and survival of COVID‐19 patients

Abstract: We aimed to examine independent predictive factors for the severity and survival of COVID‐19 disease, from routine blood parameters, especially the blood urea nitrogen (BUN)/creatinine (Cr) ratio. A total of 139 patients with COVID‐19 were investigated at Siirt State Hospital. According to the disease severity, the patients were categorized as three groups (moderate: 85, severe: 54, and critical: 20). Then, patients were divided into two groups: nonsevere (moderate) and severe (severe and critical). Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 28 publications
8
102
0
7
Order By: Relevance
“…Overall, six studies were done in China 10 , 11 , 14 17 and only one was done outside of China, in Turkey. 18 All studies compared the on-admission PLR values between severe and non-severe COVID-19 patients, except for one that compared the PLR values between severe and moderate COVID-19 patients (Table 1). 17 Unfortunately, no study explored the prognostic value of PLR on admission to predict mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, six studies were done in China 10 , 11 , 14 17 and only one was done outside of China, in Turkey. 18 All studies compared the on-admission PLR values between severe and non-severe COVID-19 patients, except for one that compared the PLR values between severe and moderate COVID-19 patients (Table 1). 17 Unfortunately, no study explored the prognostic value of PLR on admission to predict mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The possible reasons for the high heterogeneity could be due to the distinct interstudy baseline characteristics of the subjects, different number, and proportion of patients with comorbidities as well as the proportion of severe and non-severe cases. Fesih, Qu, and Sun excluded patients with other comorbidities, such as chronic lung diseases, hematological diseases, and liver diseases 10 , 16 , 18 while Gong did not provide any data on the comorbidities of the patients. 14 Another reason could be due to the small number of included studies in this meta-analysis, which could reduce the accuracy of the heterogeneity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 42 studies were further scrutinized by reading the full text. Finally, only 19 studies were included in this metaanalysis, of which 9 reported the predictive value on disease severity [26][27][28][29][30][31][32][33][34], 6 reported the predictive value on mortality [35][36][37][38][39][40], and 4 reported the predictive value on both disease severity and mortality [41][42][43][44].…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…The remaining 42 studies were further scrutinized by reading the full text. Finally, only 19 studies were included in this meta-analysis, of which 9 reported the predictive value on disease severity [26][27][28][29][30][31][32][33][34], 6 reported the predictive value on mortality [35][36][37][38][39][40], and 4 reported the predictive value on both disease severity and mortality [41][42][43][44].…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%